circCIMT Silencing Promotes Cadmium‐Induced Malignant Transformation of Lung Epithelial Cells Through the DNA Base Excision Repair Pathway - Meizhen Li; Wei Chen; Jinjin Cui; Qiuyi Lin; Yufei Liu; Huixian Zeng; Qiuhan Hua; Yihui Ling; Xiaodi Qin; Yindai Zhang; Xueqi Li; Tianshu Lin; et al. (Advanced Science)
Abstract Changes in gene expression in lung epithelial cells are detected in cancer tissues during exposure to pollutants, highlighting the importance of gene‐environmental interactions in disease. Here, a Cd‐induced malignant transformation model in mouse lungs and bronchial epithelial cell lines is constructed, and differences in the expression of non‐coding circRNAs are analyzed. The migratory and invasive abilities of Cd‐transformed cells are suppressed by circCIMT. A significant DNA damage response is observed after exposure to Cd, which increased further following circCIMT‐interference. It is found that APEX1 is significantly down‐regulated following Cd exposure. Furthermore, it is demonstrated that circCIMT bound to APEX1 during Cd exposure to mediate the DNA base excision repair (BER) pathway, thereby reducing DNA damage. In addition, simultaneous knockdown of both circCIMT and APEX1 promotes the expression of cancer‐related genes and malignant transformation after long‐term Cd exposure. Overall, these findings emphasis the importance of genetic‐epigenetic interactions in chemical‐induced cancer transformation.